2021
DOI: 10.1016/j.ejro.2020.100305
|View full text |Cite
|
Sign up to set email alerts
|

The time course of chest CT lung changes in COVID-19 patients from onset to discharge

Abstract: Highlights Patients with severe disease had higher total scores in every CT scan and scores in each lobe than non-severe patients. Typical CT image of non-severe cases mainly presented as GGO, whilst GGO mixed with consolidation was more seen in severe cases. Severe versus non-severe cases had higher prevalence of fibrosis and air bronchogram in CT scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…In addition, no significant differences in CT inflammatory images between young and elderly monkeys were obtained by CT analysis, but inflammation was observed in multiple locations in elderly monkeys, consistent with the results of study showing that the incidence of multiple ground-glass opacity was higher in elderly patients than in young patients (46)(47)(48). Moreover, the duration of inflammation in the lungs tented to be longer in the elderly CMs than in the young CMs, which is also consistent with a comparison between patients with severe symptoms and patients with nonsevere symptoms (49). Since there was no significant difference between those two groups, the accumulation of data using an NHP model will be very important for understanding the variations of pathological conditions caused by SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, no significant differences in CT inflammatory images between young and elderly monkeys were obtained by CT analysis, but inflammation was observed in multiple locations in elderly monkeys, consistent with the results of study showing that the incidence of multiple ground-glass opacity was higher in elderly patients than in young patients (46)(47)(48). Moreover, the duration of inflammation in the lungs tented to be longer in the elderly CMs than in the young CMs, which is also consistent with a comparison between patients with severe symptoms and patients with nonsevere symptoms (49). Since there was no significant difference between those two groups, the accumulation of data using an NHP model will be very important for understanding the variations of pathological conditions caused by SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 90%
“…The most common classical finding in thoracic CT of SARS-CoV-2 infected patients was Ground Glass Opacities [55]. Meta-analysis conducted by Zarifian A. et al [56] In our review, the overall incidence of crazy cave pattern is observed in 24.47 % COVID-19 patients, while the recent meta-analysis conducted by Bao C. et al [57], Zheng Y. et al [58] and Zhu J. et al [59] and Zhou X. et al [70] showed pooled percentages as 14.81 %, 24 %, [42] 305 35.6 % and 20 % respectively. Sub-pleural bands is another typical radiological feature in SARS-CoV-2 infections, and was observed as 55.61 %, in our review while the meta-analysis conducted by Zheng Y. et al 58 % of the patients developed sub-pleural bands during coronavirus disease [58].…”
Section: Discussionmentioning
confidence: 55%
“…In general, CT images in patients recovering from COVID-19 infection are known to be divided into four stages: the early stage (0–4 days), progressive stage (5–8 days), peak stage (9–13 days), and absorption stage (>14 days), although in cases with a poor prognosis, the radiological changes are not resolved and even spread [ 10 ] and, in severe COVID-19 cases, the improvement of CT images needs more time than those in nonsevere cases do [ 11 ]. Compared with the patients in these previous reports, in our patients, the severity of hypoxemia was diphasic, and the peak stage was also more delayed and prolonged.…”
Section: Discussionmentioning
confidence: 99%